Smartphone-Based Anecdotal Text Learning Media - Oki Rasdana; Silvia Permatasari; Mangatur Sinaga; Amira Deani; Amelia Putri; Dudit Nugroho (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2026)
This study aims to develop a smartphone-based anecdotal text learning media for high school students using the DDDE (Decide, Design, Development, Evaluation) model. The background of the research is based on three main problems: (1) low interest in learning conventional anecdotal texts, (2) lack of teaching materials relevant to students' digital lives, and (3) suboptimal use of smartphones (4) internet access in schools that has not been optimized. This research aims to provide innovative media alternatives based on the contextual needs of schools. The research methods used are research and development with observation, interview and data testing techniques. The data was processed using mixed method data analysis techniques. Quantitative data was obtained from the results of product trials using questionnaires and learning outcome tests, while qualitative data was obtained from observations and interviews with teachers and students. The validity of the product is assessed by material experts, media experts, and practitioners with categories that are very suitable for Indonesian learning. The trial is divided into a limited trial in one class and a field trial involving two classes at the school. The results of the analysis of 26 student samples showed an average pretest score of 61.8 and a posttest score of 83.8, with an increase of 22 points. The paired t-test yielded a calculated t of 44.9 > a t-table of 2.06 (α = 0.05), so there was a significant difference between learning outcomes before and after using the learning media. The normalized gain value (g) = 0.58 is in the moderate category, which indicates that learning media is effective in improving student learning outcomes. Thus, the media developed has proven to be very suitable for use in the learning process and has a positive effect on improving student understanding.